The Effect Of Project Based Learning Model Combined With Snake And Ladder Media To Fifth Graders’ Learning Activity And Outcomes In Social Studies - Catur Agustina Candra Dewi,; Yatim Riyanto,; Suhanadji, (Technium Social Sciences Journal, 2020)
The present study aims to determine the effect of the project based learning model with snake and ladder media to fifth graders’ learning activity and outcome in social studies. The material covered was the Proclamation of Indonesian Independence. The research method used was a quasi-experimental with non-equivalent (pretest and posttest) control group design. The research respondents consisted of 36 students. Data were collected through observation and tests. The research instrument used was observation sheet containing students’ learning activities and a test of learning outcomes that had been validated by experts. Independent samples t-test was used for hypothesis testing. The students’ activity and learning outcomes improvement were determined by the results of the N-gain test. The results showed an increase in activity and learning outcomes in both classes. The experimental class performed higher activity and learning outcomes than the control class. This shows that project based learning model with snake ladder media had a positive effect primary 5 students’ activities and learning outcomes in social studies learning.